Markers of renal tubular dysfunction measured annually do not predict risk of microalbuminuria in the first few years after diagnosis of Type I diabetes. - Schultz, C; Dalton, R; Neil, H; Konopelska-Bahu, T; Dunger, D (2001)
AIMS/HYPOTHESIS: Early detection of risk of microalbuminuria could prevent early renal damage. We investigated whether urine retinol binding protein and N-acetyl-glucosaminidase could predict the risk of microalbuminuria in a large cohort of children followed from diagnosis of Type I (insulin-dependent) diabetes mellitus. METHODS: Subjects under 16 years of age within a georaphically defined region were recruited at diagnosis of Type I (insulin-dependent) diabetes mellitus. Annually, albumin-, retinol binding protein- and N-acetyl-glucosaminidase- to creatinine ratios were each measured in 3 urine samples. RESULTS: A total of 511 subjects were followed for a median of 6 years (range: 1-14). Microalbuminuria (males: > or = 3.5 mg/mmol; females: > or = 4.0 mg/mmol, in 2 out of 3 urines) developed in 78 subjects (36 male). The cumulative probability of microalbuminuria was 40% after 12 years duration of diabetes. Retinol-binding-proteinuria (men: > or = 21 microg/mmol; women > or = 33 microg/mmol) developed in 217 subjects (152 men). The cumulative probability of retinol-binding-proteinuria was 67 % after 12 years duration of diabetes. The cumulative probability of retinol-binding-proteinuria was 40 % before the onset of microalbuminuria and 59% in subjects who did not subsequently develop microalbuminuria. Retinol-binding-proteinuria developed at a higher rate with increasing HbA1c than microalbuminuria. N-acetyl-glucosaminidase-uria (males: > or = 56 micromol-pnp x h(-1) x mmol(-1); females: > or = 46 micromol-pnp h(-1) x mmol(-1)) developed in 477 subjects. The cumulative probability of N-acetylglucosaminidase-uria was 98 % after 10 years of diabetes duration. The cumulative probability of N-acetyl-glucosaminidase-uria was 73 % in the years before the onset of microalbuminuria and 97 % in subjects without microalbuminuria. The probability of Nacetyl-glucosaminidase-uria was 99 % with an HbA1c greater than or equal to 14.5 %. CONCLUSIONS/INTERPRETATION: Raised amounts of urine retinol binding protein and N-acetyl-glycosaminidase are related to HbA1c and the duration of diabetes. They occur in the majority of subjects and are not early markers for the risk of microalbuminuria.